Students' degenerative thinking disposition on non-relational aspects in solving quadrilateral problems - Rahma Wahyu; Purwanto Purwanto; I Nengah Parta; Rustanto Rahardi (Universitas PGRI Madiun, 2023)
The urgency of this research is to see the tendency for non-generative thinking in students to solve rectangular problems, which defined as a degenerative thinking disposition. A degenerative thinking disposition is a person's tendency to take action that ignores information excessively without considering analytical and genetic characteristics in generalizing a problem. The results of the preliminary study show that there are indications of non-generative thinking when students solve problems regarding the perimeter of a rectangle. Many students point out the incompleteness of the solution to the problem of the perimeter of a quadrilateral and tend to be hasty in assuming that the quadrilateral in question is a rectangle. This included in the symptoms that do not give rise to relational aspects. This type of research is qualitative with an exploratory, descriptive approach to three subjects. The data analysis technique uses thematic analysis steps. The results of the study show that students who experience degenerative thinking dispositions from non-relationship aspects ignore information excessively. Students with non-relationship aspects tend to experience excessive information neglect when relating information to definitions and analytical and genetic properties. Students overgeneralize the problem of rectangular properties without considering the existence of other esufficient elements. The concepts used in concluding problem solutions are based on still partial concepts. So the generalizations that are used as the basis for solving other problems end up being wrong.